The Increasingly Loud Voice of Female Riﬂemen and their Visible Works: the Protocol of the First Lithuanian Women Riﬂemen’s Congress in 1933 - Nefas, Mindaugas (History / Istorija, 2020)
Annotation. The publication of scientifc sources presents the protocol of the first women’s congress held in Kaunas on July 2–3, 1933. It clarifes the state of women riﬂemen’s activities, the problems that existed, and the goals and hopes set. Tis convention marks the beginning of more progressive activities for women riﬂemen and is therefore an important source for further research into the history of women riﬂemen. Te source is accompanied by comments, clarifcations and a general overview of the activities of women riﬂemen.